Formation Algorithms and Properties of Binary Quasi-Orthogonal Code Sequence of Modern Satellite Systems - Petrovich Pashintsev, Vladimir; Anatolyevich Kalmykov, Igor; Pavlovich Zhuk, Aleksandr; Viktorovich Orel, Dmitrii; Pavlovna Zhuk, Elena (International Journal of Engineering and Technology, 2018)
Increased number of threats to user interface of navigation signals, mainly in the form of suppression of navigation signals by jamming as well as navigation signal spoofing by false signals, assumes development of counter measures including improvement of structure security of navigation signals on the basis of stochastic use of code sequences which are ranging codes. This article proves the required number of unique discrete code sequences which can improve structure security of navigation signal in global navigation satellite system upon their stochastic use. Properties of discrete quasi-orthogonal code sequences are estimated which are used and proposed for use in global navigation satellite systems with channel code division, they are compared with optimum values of code balancing, number of element series and lower bounds of maximum lateral peaks of aperiodic auto-correlation function and maximum peaks of aperiodic mutual-correlation function. The experimental results show that the minimum values of the considered correlation functions of discrete quasi-orthogonal code sequences of known global navigation satellite systems exceed the lower bound by 3â€“6 times. The performances of code balancing and element series of discrete quasi-orthogonal code sequences of the known global navigation satellite systems satisfy in average the allowable intervals. The number of source lines of discrete quasi-orthogonal code sequences of the known global navigation satellite systems is significantly lower than their umber required for improvement of structure security of navigation signal based on their stochastic use. On the basis of the revealed drawbacks of the known discrete quasi-orthogonal code sequences, the necessity to develop new methods is substantiated allowing to obtain their required number together with statistic properties comparable with the best values of discrete quasi-orthogonal code sequences applied as navigation signals in global navigation satellite systems.Â Â